Pendampingan Manajemen Operasional pada Usaha Kupi Aceh di KA Kupi - Putri Wahyuni; Dedy Lazuardi; Ihdina Gustina (Mitra prima, 2026)
This activity aims to improve partners' ability to manage business operations more effectively and efficiently. The methods used include identifying problems through observation and interviews, followed by mentoring in the form of education, training, and hands-on practice in preparing SOPs, structuring workflows, and maintaining operational records. The results of the activity indicate an increase in partners' understanding of managing business operations, the development of simpler SOPs, and improvements to a more systematic workflow. Furthermore, partners have begun implementing more organized and consistent operational records, making it easier to control business activities. This activity has had a positive impact on improving the quality of operational management and supporting the sustainability of Kupi Aceh's business on the KA Kupi.